Analysis of the causes and level of maintenance for enterprise systems in construction companies - Lee, Chijoo; Lee, Chiheyon; Lee, Eul-Bum (Journal of Civil Engineering and Management, 2018)
A construction company without a similar information technology (IT) system in the past has insufficient historical data to use for investment decision-making of IT system. An estimation of maintenance costs is especially more uncertain than the initial investment costs, and the uncertainty is greater when the IT system is used over a long period, such as an enterprise system (ES). This study proposes estimation criteria for the maintenance costs of an ES for an accurate investment decision. First, the causes of maintenance are determined, and the level of maintenance analyzed. Then, the result is compared with a general trend of maintenance incidence (bathtub curve) that is widely used as reference criteria to estimate maintenance cost. The level of maintenance was high during the early stage but steadily decreased in the middle and end stage because high-cost maintenance activities were postponed with the approach of the time in which the ES was being restructured. This trend is different from the bathtub curve that increases again during the end stage. Thus, when a maintenance contract is negotiated, the maintenance level that affects maintenance cost should be considered as well as the incidence of maintenance.